1978
DOI: 10.1037/0012-1649.14.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in children's recognition memory for faces.

Abstract: Children at three age levels were tested for recognition memory of adult male faces following three different orienting activities at encoding. One group received standard intentional learning instructions, another group judged whether or not each face had a big nose, and a third group judged whether or not each face appeared "nice." Memory improved with age, and judgments of niceness facilitated memory equally at all ages. The results pose difficulties for Brown's model of memory development proposed in 1975.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 8 publications
5
32
0
Order By: Relevance
“…This is entirely consistent with previous research (e.g., Blaney & Winograd, 1978;Carey et al, 1980;Flin, 1985). Curve fitting revealed that upright face recognition improved more reliably with age than inverted face recognition.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is entirely consistent with previous research (e.g., Blaney & Winograd, 1978;Carey et al, 1980;Flin, 1985). Curve fitting revealed that upright face recognition improved more reliably with age than inverted face recognition.…”
Section: Discussionsupporting
confidence: 81%
“…Through four Experiments we have shown that there was a significant improvement in the recognition of upright faces with development (both longitudinally and cross sectionally) consistent with previous research (Blaney & Winograd, 1978;Carey et al, 1980;Goldstein, 1965;Goldstein & Chance, 1964;Saltz & Sigel, 1967). The longitudinal data showed numerically consistent results with the cross-sectional data for participants within three years.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Face recognition abilities improve through childhood (e.g. Blaney & Winograd, 1978;Ellis & Flin, 1990;List, 1986). This improvement may follow a linear pattern (Feinman & Entwisle, 1976;Hills, 2014) and is associated with better memory for faces in children (Dempster, 1981;Hills 2012) and faster responding (Johnston & Ellis, 1995).…”
Section: Development Of Face-spacementioning
confidence: 99%
“…Visual-processing accounts argue that facilitation arises as a function of the quantity or quality of visual information encoded about the face. Facilitation may be due to a greater number of features being attended to and stored during encoding (the feature quantity account; e.g., Blaney & Winograd, 1978;Courtois & Mueller, 1979;Winograd, 1978Winograd, , 1981 or to the encoding of more holistic impressions of the face (i.e., the interrelations between features), in addition to feature-based information (the holistic account; e.g., Berman & Cutler, 1998;Wells & Hryciw, 1984). Alternatively, semantic-processing accounts suggest that facilitation may be due to the addition of semantic associations to the described face, which benefit retrieval (e.g., Anderson & Reder, 1979;Bruce & Young, 1986;Ryan & Schooler, 1994, cited in Schooler, Ryan, & Reder, 1996.…”
mentioning
confidence: 99%